2019
DOI: 10.18388/abp.2018_2771
|View full text |Cite
|
Sign up to set email alerts
|

Dietary quercetin abrogates hepatorenal oxidative damage associated with dichloromethane exposure in rats

Abstract: Exposure to dichloromethane (DCM), a commonly used chlorinated solvent in industrial settings and for the production of many household products, reportedly elicits detrimental effects in animals and humans. The present study investigated the protective role of dietary quercetin on DCM-induced hepatorenal damage in rats. Experimental rats were orally administered with DCM (150 mg/kg) and 30 min later with quercetin at 10, 20 and 40 mg/kg or none for 7 consecutive days. The results indicated that DCM-mediated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Quercetin, also known as 3,5,7,3′,4′-pentahydroxyflavone, is a natural flavonoid compound. In nature, it exists in various forms in different plants and can be found as either quercetin aglycone or derivatives, while the most abundant form in the diet is glycosides (Owumi et al, 2019). Quercetin is highly soluble in lipids and alcohol.…”
Section: Pharmacokinetics and Bioavailability Of Quercetinmentioning
confidence: 99%
“…Quercetin, also known as 3,5,7,3′,4′-pentahydroxyflavone, is a natural flavonoid compound. In nature, it exists in various forms in different plants and can be found as either quercetin aglycone or derivatives, while the most abundant form in the diet is glycosides (Owumi et al, 2019). Quercetin is highly soluble in lipids and alcohol.…”
Section: Pharmacokinetics and Bioavailability Of Quercetinmentioning
confidence: 99%
“…The chemoprotective effect of various polyphenolic compounds has been widely reported [ 29‐33 ] against cellular injury. Polyphenol confers protective benefits against chemical damage to cells, [ 34‐36 ] disease onsets such as cancer, [ 37,38 ] and neurological syndromes. [ 39‐41 ] Rutin, a flavonol glycoside is present in numerous plants and vegetables, [ 38 ] flavonol help in the revival of body cells, disinfects, and perform anti‐inflammatory, antidepressant, and antiviral function.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results of El-Nekeety et al's study, which reported that treatment with quercetin at two tested doses 50, and 100 mg/kg BW overcome the biochemical and histological changes in a dose-dependent manner in rats fed aflatoxin-contaminated diet [5]. This is also inconsistent with Owumi et al's study, which stated that treatment with 40 mg/kg quercetin in dichloromethane-treated rats caused significantly decreased near-normal values of the serum ALT, AST [21].…”
Section: Figure (5): Liver Of Rat From Group іᴠ Showing Interface Hep...mentioning
confidence: 80%
“…Our results are inconsistent with the results of Himri et al, and Abo EL-Sooud et al's study, where a significant increase was observed in serum creatinine but serum urea concentration showed no significant increase after treatment with 3, 7.5 mg/kg tartrazine. These results referred to a low dose of the used tartrazine [17][18][19][20][21][22][23].…”
Section: Figure (5): Liver Of Rat From Group іᴠ Showing Interface Hep...mentioning
confidence: 99%